Population dynamics of the pharaoh cuttlefish Sepia pharaonis (Mollusca: Cephalopoda) in the Arabian Sea coast of Oman - Mehanna, Sahar Fahmy; Al-Kharusi, Lubna; Al-Habsi, Saoud (Indian Journal of Fisheries, 2013)
The stock of pharaoh cuttlefish Sepia pharaonis was assessed based on 4616 specimens (1895 males, 2051 females and 670 unsexed), collected during the demersal fishery survey in the Arabian Sea coast of Oman between September 2007 and August 2008 and from November 2011 to June 2012. Age and growth were studied based on length frequency data using Bhattacharya’s method. There was no significant difference in growth between sexes and the longevity was estimated to be five years for mantle length (ML) range 1.7 – 44 cm. The estimated von Bertalanffy growth parameters were L∞ = 46.21 cm ML, K = 0.52 y -1 and t 0 = 0.1 y. The instantaneous rates of total (Z), natural (M) and fishing (F) mortalities were 2.57, 0.997 and 1.57 y -1 respectively with exploitation rate (E) of 0.61 and exploitation ratio (U) of 0.66. The estimated ML at first capture (L c ) was 12 cm, while the ML at first sexual maturity (L m ) was 19.60 cm. The yield per recruit model revealed that S. pharaonis stock in the Arabian Sea is heavily exploited, but has a scope to increase the yield by increasing the length at first capture to be not less than 20 cm ML. Also, there is an urgent need to protect juveniles and under-sized part of the stock.